Inequality and governance in the metropolis - Sellers, Jefferey M. ; Arretche, Marta ; Kübler, Daniel ; Razin, Eran (Palgrave Macmillan, 2020)
This book undertakes the first systematic, multi-country investigation into how regimes of place equality, consisting of multilevel policies, institutions and governance at multiple scales, influence spatial inequality in metropolitan regions. Extended, diversified metropolitan regions have become the dominant form of human settlement, and disparities among metropolitan places figure increasingly in wider trends toward growing inequality. Regimes of place equality are increasingly critical components of welfare states and territorial administration. They can aggravate disparities in services and taxes, or mitigate and compensate for local differences. The volume examines these regimes in a global sample of eleven democracies, including developed and developing countries on five continents. The analyses reveal new dimensions of efforts to grapple with growing inequality around the world, and a variety of institutional blueprints to address one of the most daunting challenges of twenty-first century governance.Contents: Metropolitan inequality and governance : a framework for global comparison Jefferey M. Sellers -- Contested metropolis : inequality and the multilevel governance of metropolitan regions in the USA Jefferey M. Sellers, Erika R. Petroy, and Sasha Hondagneu-Messner -- Metropolitan governance and social inequality in India Annapurna Shaw -- Metropolitanization, urban governance, and place (in)equality in Canadian metropolitan areas R. Alan Walks -- "Tamed Tieboutianism" and spatial inequalities in Swiss metropolitan areas Daniel Kübler and Philippe E. Rochat -- Place equality regimes and municipal choices in metropolitan Spain : regional institutions and local political orientations Clemente J. Navarro, María Jesús Rodríguez-Garcia, Cristina Mateos, and Lucía Muñoz -- The Brazilian place equality regime Marta Arretche -- The mosaic of local governments in post apartheid South Africa : municipal asymmetries and spatial inequality Helder Ferreira do Vale and Robert Cameron -- Interlocal disparities in Israel's metropolitan areas : the impact of crisis and recovery in a neoliberal regime Eran Razin -- Place equality regime(s) in French city regions Deborah Galimberti and Gilles Pinson -- Socio-spatial inequalities in the Czech metropolitan areas : the case of Prague metro Tomáš Kostelecký and Jana Vobecká -- The equal metropolis? : can social policies counteract diversity in Swedish metropolitan settings? Anders Lidström.